The Honorific of Gamkonora Language: A Study of Sociolinguistics - Ibrahim, Ratu Balgis; Muhamad, Hujaefa Hi.; Lestari, Sri Ayu Budi (Borong Newinera Publisher, 2024)
This study aims to identify and document the use of honorifics in the Gamkonora language, a non-Austronesian language used by the Gamkonora community in West Halmahera, North Maluku. The research method is descriptive qualitative with a sociolinguistic approach. Data were obtained through in-depth interviews, direct observation, and conversation recordings from various social contexts, such as family, education, and religion. The results of the study indicate that the Gamkonora language has a complex honorific system, including referential and addressee honorifics, which reflect social norms and hierarchical structures in its community. The use of honorifics is influenced by factors of social status, age, kinship, and formal or informal situations. This study not only contributes to the documentation of endangered regional languages, but also provides insight into the relationship between language and social structure in the Gamkonora community.